2015
DOI: 10.1111/1756-185x.12728
|View full text |Cite
|
Sign up to set email alerts
|

Does the buck stop with the bugs?: an overview of microbial dysbiosis in rheumatoid arthritis

Abstract: The human body is an environmental niche which is home to diverse co-habiting microbes collectively referred as the human microbiome. Recent years have seen the in-depth characterization of the human microbiome and associations with diseases. Linking of the composition or number of the human microbiota with diseases and traits date back to the original work of Elie Metchnikoff. Recent advances in genomic technologies have opened up finer details and dynamics of this new science with higher precision. Microbe-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 108 publications
1
42
0
2
Order By: Relevance
“…It has been hypothesized that dysbiosis of the microbiome could lead to local inflammation, loss of barrier function, and bacterial translocation from mucosa to the bloodstream. Some bacterial cell wall components might molecularly mimic human autoantigens, triggering an immune response also directed against the joint [20, 21]. …”
Section: Risk Factorsmentioning
confidence: 99%
“…It has been hypothesized that dysbiosis of the microbiome could lead to local inflammation, loss of barrier function, and bacterial translocation from mucosa to the bloodstream. Some bacterial cell wall components might molecularly mimic human autoantigens, triggering an immune response also directed against the joint [20, 21]. …”
Section: Risk Factorsmentioning
confidence: 99%
“…In addition, Prevotella also appears to correlate with other microbial differences between lean and obese adults, associated with both the overall bacterial composition and digestive efficiency (23,24). In contrast to these seemingly positive effects, some clinical studies concluded that elevations in Prevotella may be a signature feature of the dysbiosis seen in autoimmune conditions, such as rheumatoid arthritis (25–27). …”
Section: Introductionmentioning
confidence: 99%
“…Recent findings demonstrate that alteration in the equilibrium among commensal bacteria is associated not only with Inflammatory bowel disease (IBD), allergy, diabetes and celiac disease (Cheng et al, 2013), but also with rheumatoid arthritis (Vaahtovuo et al, 2008; Sandhya et al, 2016; Scher et al, 2016). …”
Section: Introductionmentioning
confidence: 99%